Factorial design analysis of parameters for the sorption-enhanced steam reforming of ethanol in a circulating fluidized bed riser using CFD. Issue 43 (5th July 2018) - Phuakpunk, Kiattikhoon; Chalermsinsuwan, Benjapon; Putivisutisak, Sompong; Assabumrungrat, Suttichai
Abstract : The sorption-enhanced steam reforming of ethanol (SESRE) has recently been reported as a novel process for hydrogen (H2 ) production. Abstract : The sorption-enhanced steam reforming of ethanol (SESRE) has recently been reported as a novel process for hydrogen (H2 ) production. SESRE can operate well on a Ni-based catalyst with dolomite as a sorbent in packed-bed reactors. In this study, the circulating fluidized bed (CFB) concept was proposed to obtain higher productivity and continuous operation of SESRE. Particular focus was directed to the design and selection of suitable operating conditions of the CFB riser. Two-dimensional transient models using the Euler–Euler approach and the kinetic theory of granular flows were applied to investigate the H2 production performance from a pilot-scale riser. The 2 k full factorial design method was utilized to examine the significances of five specific parameters, namely, the riser diameter, inlet temperature, catalyst-to-sorbent ratio, solid flux, and inlet gas velocity on two response variables, namely, H2 purity and H2 flux. From the ANOVA results, either the main effect or the interactions of each parameter were shown to be significant on both the H2 purity and the H2 flux, particularly the riser diameter and the solid flux. For optimizing the operation and reaction parameters, the best case was the system with riser diameter of 0.2 m, inlet temperature of 600 °C, catalyst-to-sorbent ratio of 2.54 kg kg −1, solid flux of 200 kg m −2 s −1, and gas velocity of 3 m s −1, obtaining H2 purity of 91.30% on a dry basis with a significantly high H2 flux of 0.147 kg m −2 s −1 . The hydrodynamics showed that SESRE reached breakthrough within the bottom dense zone. However, incomplete conversion occurred in the core of the riser because of the very dilute bed.